1994
DOI: 10.2307/1369113
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Cytochrome b Sequence Variation in Estimation of Phylogeny in the Vireonidae

Abstract: A recent phylogenetic study of the genus Vireo, based on protein electrophoresis, shows the taxon is polyphyletic and contains four distinct groups. This contradicts the traditional classification of the genus. Johnson et al. (1988) find a group containing members of the subgenera Vireo and Lanivireo. a lone taxon containing the species V. bellii and a division of the subgenus Vireosylva into a gilvus and an olivaceus group. To test these results independently, sequence data from the mitochondrial cytochrome b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 31 publications
1
22
1
Order By: Relevance
“…Pachycephalidae (401,(431)(432)(433)(434)(435); Paradisaeidae (436)(437)(438)(439); Rhipiduridae (440,441); Vangidae (442)(443)(444)(445); Vireonidae (446)(447)(448)(449)(450)(451) …”
Section: Sylviorthorhynchus Is Nested Within Leptasthenura Limnoctitesmentioning
confidence: 99%
“…Pachycephalidae (401,(431)(432)(433)(434)(435); Paradisaeidae (436)(437)(438)(439); Rhipiduridae (440,441); Vangidae (442)(443)(444)(445); Vireonidae (446)(447)(448)(449)(450)(451) …”
Section: Sylviorthorhynchus Is Nested Within Leptasthenura Limnoctitesmentioning
confidence: 99%
“…As such, an Old World origin of idae implies at least one colonization of the New World (Cicero and 68 Johnson, 2001;Johnson et al, 1988;Reddy and Cracraft, 2007). 69 Knowledge of relationships within Vireonidae remains incom-70 plete due to taxonomically limited sampling in vireonid phyloge-71 netic studies to date (Cicero and Johnson, 2001;Johnson et al, 72 1988; Murray et al, 1994;Sibley and Ahlquist, 1982). Other molec-73 ular studies of vireonid relationships used denser sampling but 74 either limited their scope of inquiry to species complexes of inter-75 est (Cicero and Johnson, 1998;Johnson and Zink, 1985;Johnson, 76 1995) or examined phylogeographic variation within single species 77 (Cicero and Johnson, 1992;Zink et al, 2010).…”
mentioning
confidence: 99%
“…Both species 385 are atypically dark-plumaged vireos with a history of taxonomic 386 uncertainty. Hamilton (1962) placed the migratory, shrub-nesting 387 V. atricapilla within the more arboreal V. solitarius complex on 388 account of plumage similarities, but a preliminary phylogenetic 389 study did not consistently resolve a placement for V. atricapilla 390 (Murray et al, 1994). The sedentary Mexican endemic V. brevipennis 391 was described as the monotypic genus Neochloe (Sclater, 1857) and 392 despite subsequent lumping with Vireo it has remained difficult to 393 place taxonomically (Hamilton, 1962;Phillips, 1962 V. bellii shares affinities with the ''eye-ringed'' clade (Brewer and 398 Orenstein, 2010).…”
mentioning
confidence: 99%
“…Although relatively short internodes appear to separate vireonids from other groups, and different genera within Vireonidae, both allozymes (Johnson et al, 1988) and mtDNA (Murray et al, 1994;Cicero and Johnson, 1998; this study) have shown exceptionally large divergences-i.e., large genetic distances and long terminal branches-within the family at the species or genus level. This finding is consistent with an early radiation.…”
mentioning
confidence: 56%
“…Because 28 CICERO AND JOHNSON the number of potential taxa for this study is enormous, we focused our sampling on (1) groups that traditionally have been considered close relatives of the Vireonidae, i.e., members of the Parulidae and Laniidae, and (2) discrete groups that are undisputed members of the Corvida and Passerida (families Corvidae and Passeridae, respectively). To obtain a broad representation of taxa within these oscine families, and to minimize problems with long branches (Lyons-Weiler and Hoelzer, 1997), we sequenced at least two individuals per family and, where possible, included representatives of different genera or clades (e.g., eye-ringed and eye-lined clades of Vireo; Murray et al, 1994;Cicero and Johnson, 1998 and unpublished). Eye-ringed and eye-lined vireos have been recognized as separate subgenera (American Ornithologists' Union, 1983), although this distinction was not supported by allozymes (Johnson et al, 1988;American Ornithologists' Union, 1998).…”
Section: Taxa and Genes Examinedmentioning
confidence: 99%